If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 3(x + -4) = 27 Reorder the terms: 3(-4 + x) = 27 (-4 * 3 + x * 3) = 27 (-12 + 3x) = 27 Solving -12 + 3x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 3x = 27 + 12 Combine like terms: -12 + 12 = 0 0 + 3x = 27 + 12 3x = 27 + 12 Combine like terms: 27 + 12 = 39 3x = 39 Divide each side by '3'. x = 13 Simplifying x = 13

| 12*x+4=2 | | 4+2=0 | | 2+7+5=5 | | 7-6x=2x-9 | | 42x+12=20 | | 4(2)+12=20 | | 4y-3=37 | | 1.2x=2.3x-2.2 | | 15x=11x+25 | | (2+3)6= | | 15x+11x=25+11x+11x | | 3(x+9)= | | -2(5-3)= | | 5.3+2.8+3.7+6.2= | | (9y-6)(-3)= | | 14+x=21 | | 26x=25+22 | | 3x=36-5x | | 4(x+4)=6(x-2) | | 6x+7=-5 | | -9t+2=56 | | -69=7v-6 | | 35=-2y-15 | | 4-3n=43 | | 12-5u=48 | | -27+20w=73 | | 13=5-8m | | 11r+60=16 | | y-24=-7 | | 23-x=13 | | -14r-7=49 | | 25a-4=96 | | 60y-7=173 | | 7x+3=-4 | | 23y+6=75 | | 17a+9=77 | | -2m+9=7 | | 8a-7=65 | | b-4=72 | | 52x+4=-100 | | -6z+15=3 | | 2(a+5)=2(a-3) | | 8+19y-1=8y+124-24 | | 2x+4y=8 | | 9+8x=7-5x | | 4k-10=14 | | 4n+8=3n+10 | | 3x+4=2x+7 | | 14=2n-4 | | k+3=8 | | 3(a+5)=24 | | n-4=10 | | 5(r+4)=45 | | 6x-7=41 | | x+5=-3 | | 2x+4x+10=12 | | 4(x+-7)+12=20 | | 9x=63 | | 14x-13=9x+1 | | 11x=22 | | z-9=63 | | 7k=4k+12 | | 4j+3=11 | | t+7=13 | | 7r-5=23 |